What's new in soft tissue and bone pathology 2022-updates from the WHO classification 5th edition - Erica Y. Kao; Jose G. Mantilla (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
The 2020 release of the WHO Classification of Soft Tissue and Bone Tumors, 5th edition, contains several changes driven by new knowledge in the field. These include reclassification of some entities, refinement of risk classification systems, and the inclusion of novel disease processes, many of which are driven by recurrent gene fusions. The most notable changes are described here.